2022
DOI: 10.1093/fqsafe/fyac028
|View full text |Cite
|
Sign up to set email alerts
|

A novel edible packaging film based on chitosan incorporated with persimmon peel extract for the postharvest preservation of banana

Abstract: This study aimed to develop a novel edible packaging film for the postharvest preservation of banana based on chitosan (CS) and persimmon peel extract (PPE). Scanning electron microscopy (SEM) analysis showed PPE was evenly distributed in the CS matrix and Fourier transform infrared (FT-IR) spectroscopy analysis showed CS and PPE interacted to form hydrogen bonds, demonstrating good compatibility. Simultaneously, the addition of PPE also significantly improved CS film's physical properties and antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Chitosan is semi-crystalline in the solid phase, and its dissolution requires a dilute organic acid medium [11]. The barrier properties such as oxygen and water vapour permeability and mechanical properties of chitosan are weak [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is semi-crystalline in the solid phase, and its dissolution requires a dilute organic acid medium [11]. The barrier properties such as oxygen and water vapour permeability and mechanical properties of chitosan are weak [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…This enzymatic browning reduces bananas' preservation time, deters consumers from purchasing them, and increases banana waste [33]. Last year's studies showed that CS-based active coatings could extend bananas' preservation period and protect them from enzymatic browning [34].…”
Section: Introductionmentioning
confidence: 99%